Hypoallergenic unicompartmental knee arthroplasty and return to sport: comparison between Oxidized Zirconium and Titanium Niobium Nitride - Monti, Lorenzo; Franchi, Manuele; Ursino, Nicola; Mariani, Ilaria; Corona, Katia; Anghilieri, Filippo Maria; D'Ambrosi, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
Background: The present study aims to compare the rate of return to sports in patients who underwent surgery for mobile-bearing UKA with either hypoallergenic TiNbN or with oxidized zirconium alloy implants. Methods: The records of two consecutive cohorts for a total of 90 hypoallergenic implants were prospectively analysed. The first cohort consisted of 41 consecutive series of medial mobile-bearing hypoallergenic TiNbN UKA, whereas the second cohort consisted of 49 consecutive medial fixed-bearing hypoallergenic Uni Oxinium.The clinical evaluation involved evaluating each patient’s University of California, Los Angeles (UCLA) activity scoresand the High-Activity Arthroplasty Score(HAAS). Each patient was clinically evaluated on the day before surgery (T0), then after a minimum follow-up period of 12 months (T1), and finally after 24 months (T2). Results:The only pre-operative difference between the two groups involved pre-operative BMI with significantly higher BMI in TiNbN Group (p<0.001). Both groups reported significant improvement at each follow-up compared with the previous and also at the final follow up with respect to UCLA and HAAS (p<0.05), except for UCLA in TiNbN between T1 and T2(p>0.05). Moreover, BMI improved significantly at the final follow up, but only in TiNbN group (p<0.05). Conclusions:Both TiNbN and Oxinium UKA procedures enabled patients to return to an acceptable level of sports activity with excellent radiographic outcomes after the final follow up regardless of the age, gender, BMI, and bearing type.